PELAKSANAAN PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL OLEH DINAS SOSIAL DI DESA SELAT BARU KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2010-2014 - Akhyar Ferika; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Since the 1990s, the attention of the community began to burst in particular for remote indigenous communities in Indonesia. The concern among others, looks at several things, first, changes in the terms or the negative designations such as indigenous peoples, communities and other backward into Remote Community Community or Remote Indigenous Community (KAT). According to Presidential Decree No. 111 of 1999 on the Development of Social Welfare KAT, and Kepmensos No. 06 / PEGHUK / 2002 on Remote Indigenous Community Empowerment, remote indigenous communities is a social group (culture) is local and dispersed and less or not participate in the network and good service social, economic, political. Secondly, the recognition of the government in the form of recognition of the existence of remote indigenous communities, recognition of social and economic rights of remote indigenous communities, recognition of traditions and customs protection of remote indigenous communities and recognition of remote indigenous community empowerment program through national and regional laws that protect the rights of communities remote indigenous as well as the state's obligation to recognize and protect the rights of remote indigenous communities. This study used a qualitative descriptive qualitative research to try to explore and break through the symptoms to interpret the problems or a combination of the various problems as presented situation. This study has a Social Service Bengkalis subject while the subject is Remote Indigenous Community Empowerment Program in Desa Selat Baru. The technique of collecting data through observation, literature study and interviews. The results of research in the field found that the implementation of Remote Indigenous Community Empowerment Program by the Department of Social Welfare as the responsible agency runs quite well even though there are internal and external problems that become an obstacle. The community provides a good response to the program implemented. Social Service tries hard to be able to assist and facilitate Indigenous in order to continue to grow and decent living. But it turned out to have some constraints that hinder the passage of the program. These factors include limited funding, lack of awareness of the individuals themselves, the lack of knowledge of indigenous peoples and various other problems. Keywords: Social Services, Remote Indigenous Community Empowerment, Indigenous, Desa Selat Baru.